Grounding Detector Berbasis Mini PC pada Kapal Penumpang 250 GT di Perairan Sumenep - Romadhoni Fitriansyah; Iqlima Maulina; Akh Maulidi (INOVTEK POLBENG, 2021)
Raas Island is an island located in the Sumenep area, there is a small port as a berth for ships that usually visit the island. At the island's port, a ship accident in the form of grounding occurred which occurred on the KM. Express Bahari in the form of a 250 GT fast passenger ship, due to by sudden tides and no means of knowing it.In this reaserch will be carried out the design of safety equipment to prevent grounding on the 250 GT ship. The components used in the series of grounding deterrents on this ship are the Ultrasonic proximity sensor, Mini PC as the processor, and the output uses an LCD to display the results, the LED, and the Buzzer as a warning. To support the design of this grounding deterrent, the data used as a reference is from the KM. Express Bahari, such as ship data and the main size of the ship.The results of this tool are in the form of information and warnings in the form of the depth passed by the ship, there are 3 conditions detected by this tool, namely, Safe Conditions, Alert Conditions, and Danger Conditions. For safe conditions, the LCD on the device displays "SAFE" and the green LED is ON. For the standby condition, the LCD on the device displays the words "ON" and the yellow LED is ON. For dangerous conditions, the LCD on the device displays the words "DANGER", the red LED is ON and the Buzzer is ON